Enhancement of androstadienedione production from progesterone by biotransformation using the hydroxypropyl-beta-cyclodextrin complexation technique - Manosroi A. (2014)
The enhanced production of androstadienedione (ADD) from progesterone (P) using the hydroxypropyl-beta-cyclodextrin (HPbetaCD) complexation technique by biotransformation was demonstrated. The microorganisms used were Bacillus sphaericus ATCC 245, B. sphaericus ATCC 7063, B. sphaericus ATCC 13805, Arthrobacter simplex ATCC 6946, B. sphaericus TISTR 670 and those screened from soils in Chiang Mai Province, Thailand which were B. sphaericus SRP I, B. sphaericus SRP II and B. sphaericus SRP III. The complexed (P-complex) and the uncomplexed P at 0.3-1.2mg/ml were investigated. Samples were withdrawn from the bioconversion mixture at various time intervals for 168 h. The ADD and P contents were determined by HPLC. All organisms showed ADD production from either P or P-complex by one-step biotransformation (including side chain cleavage and dehydrogenation). At 0.3mg/ml of P in the systems of B. sphaericus ATCC 13805, A. simplex ATCC 6946 and B. sphaericus ATCC 245, the uncomplexed form showed the highest ADD yield of 2.82, 1.63 and 64.67% at 168, 168 and 144 h, whereas P-complex gave 98.44, 19.58 and 97.10% at 144, 24 and 168 h, respectively. This indicated an increase of ADD production from the P-complex in comparison to P of 35, 12 and 1.5 times, respectively. This study has shown that the complexation of P with HPbetaCD enhanced the ADD production in a novel one-step bioconversion.